Anthropogenic spherules in Zuari estuary, south west coast of India. (June 2019) - Shetye, Suhas S.; Rudraswami, N.G.; Nandakumar, K.; Manjrekar, Saiprasad
Abstract: In this study we report silica rich anthropogenic spherules from the marine environment. We found spherical, dumbbell, teardrop and fused spherules in Zuari estuary (near the Dona paula jetty), south west coast of India. The spherules were composed of SiO2 (69.8%), Na2 O (13.2%), CaO (8.8%), MgO (3.8%), and traces of Al2 O3, and FeO. Their high Na and Ca contents rules out the possibility of being an impact spherule or microtektite, or anthropogenic spherules coming from fly ash. Their elemental composition suggests that these are glass micro beads that have many applications including production of road and pavement marking materials, such as traffic paints. Considering that the glass micro beads are known to have high concentrations of Pb, As, and Sb that can leach into the marine environment, this study also raises questions regarding the impact of such spherules on marine biota, and highlights the need for further detailed study. Highlights: Silica rich anthropogenic spherules reported from the marine environment. The spherules were composed of SiO2 (69.8%), Na2 O (13.2%), CaO (8.8%), MgO (3.8%), and traces of Al2 O3, and FeO. Their high Na and Ca contents rules out the possibility of being an impact spherule or microtektite, or anthropogenic spherules coming from fly ash. Their elemental composition suggests that these are glass micro beads. Glass micro beads are known to have high concentrations of Pb, As, and Sb that can leach into the marine environment.